Characterization of the Root-Knot Nematodes Infecting Olive Trees (NTU Journal of Agriculture and Veterinary Science, 2024)
This study was conducted in 2022–2023 to identify the plant parasitic nematodes that infect olive trees. A field survey was conducted in the most olive-growing areas in Bashiqa and Al-Fadhiliya, Nineveh Governorate, Iraq. The results recorded the parasitism of the nematode Meloidogyne javanica on the olive roots. The formation of root knots on the roots was the main disease symptom. The phenotypic characteristics and perineal pattern of adult females indicated M. javanica, which was used to identify the species. DNA barcoding of the 18SrDNA gene with the primer sets 18S-530R and 18S-CL-F3 yielded a 494-bp fragment to identify M. javanica. The sequence blasted with the GenBank database gave a maximum similarity of 97% to the global isolates. The sequence was submitted and deposited with the NCBI as an Iraqi isolate under accession number PP273501. This is considered the first record of M. javanica on olive trees in Nineveh Governorate.